"Amnesia of the moment" in environmental education. Issue 2 (3rd March 2020) - Payne, Phillip G.
Abstract: Northern theories like "new materialism" and "posthumanism" are, increasingly, influential in the global productions of knowledge in environmental education (EE). In this latest discursive phase of textualising EE, the conceptual mash of "new/post" idea(lism)s is easily identified, but not critically examined, as is undertaken here via three interrelated critical case studies of key idea(l)s in the new/post. Criticism of the current normative, theoretical, methodological, and empirical mess of environmental education research (EER) must be understood within three historical and structural problems, namely; (i) the formative stages of modern EE in the 1970s, (ii) the escalating importance of theory in the 1990s transition from modern thought to postmodern thinking, (iii) the neo-liberalization of academic identity formations and post-intellectual relations in the audit culture of the corporate university of the 2000s. The first two closely related case studies of the new/post highlight the ahistorical and atheoretical mash of performatively-driven abstract theorizing in EE. Each demonstrates how earlier "founding" policy of EE, its implied pedagogical praxis, and commensurable methodological development in EER have been forgotten. The first critique focusses historically on the allegedly new idea of "agential relations" and its confused discursive claims about "action". Forgotten is the vital matter of "ecology" and its relational "things". The second rescues the ecofeminist notion of "embodied materialism". Ecofeminist praxis has been de activated by the new/post abstr action of feminist poststructural knowledge claims on "material-discursive practices". Together, these interrelated critiques retrieve a much needed historical-critical-material frame from which new/post textualism can be conceptually reconstructed and empirically qualified in ways that re activate the ecopolitical rationale for founding EE. If, indeed, theory is needed in ecopedagogical praxis, an alternative case exists for "bringing theory back in" via, for example, ecophenomenology, ecological anthropology, and ecohumanism. Ecopedagogical practices and their research might then (re)"turn" to a realist ontology via, for example, the "materialisms" of the "new" of "speculative realism" coupled with the "old" (sic) of "critical realism" in, strangely, "post post" claims on knowledge production. At issue in de-abstracting, re-materializing, repoliticizing, and decentering the hubristic authority of theory in new/post EER are numerous axiological commitments, epistemological issues, and methodological dilemmas concerning the onto ∼ ethics ∼ politics of (mis)representation in the global North. Underpinning the two case critiques is a third "criticism" of the postmodern means (mediums/modes) of knowledge production (forms) as they "intersectionally" perform a digitally platformed and instrumental colonization of the global North and South discourse of EER. "Other" wise, in the post-intellectual climate change of a universalizing newtechnics of "agentialism, ", we misrecognize who we are textually "becoming" and, in being so post-inscribed and newly-mediated, are distr acted from what "really" practically matters in the field, and why it "materially" exists.